Time domain phase noise synthesis for system simulation - Yang, L.; Yue, J.; Ehm, Henning (49th IEEE International Midwest Symposium on Circuits and Systems, 2007)
In order to verify the system performance of large-scale integrated chip sets for wireless applications, models are required to synthesize phase noise in discrete time. This paper proposes a scheme that generates phase noise in the time domain with a simple white noise input and is parameterized by quantities whose value can be adjusted to reflect the desired phase noise parameters. Furthermore, it allows selecting different combinations of noise frequency response in different frequency bands. Therefore, the noise measured in the laboratory from test chips can be easily simulated for verification of system performance. The MATLAB simulation environment was selected because of its wide application for development and evaluation of communication algorithms.
elib2cris::1512001600,yang2007